1993
DOI: 10.1021/ma00064a035
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of suspension poly(vinyl chloride). Small-angle neutron scattering of rigid and plasticized suspension PVC

Abstract: A comprehensive SANS study on both rigid and plasticized suspension PVC demonstrates the presence of superstructural order in this polymer. Comparison of the experimental scattering invariant data with a tentative two-phase model points to specific penetration of the plasticizer in the noncrystalline regions of PVC. Thermal experiments manifest the gradual and thermoreversible melting of the crystalline regions at temperatures above 80-90 °C. Uniaxial deformation experiments on plasticized PVC confirm the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…In this case the Porod plot shows the characteristic upturn at the low-q part of each setting. This has been observed for a granular PVC powders [17].…”
Section: Porod Scatteringsupporting
confidence: 56%
“…In this case the Porod plot shows the characteristic upturn at the low-q part of each setting. This has been observed for a granular PVC powders [17].…”
Section: Porod Scatteringsupporting
confidence: 56%
“…3-6, 8, 9͒ and SANS. 5,7 In order to characterize the correlation peaks in the simplest way, the contribution at very low Q-values, B(Q,T), may be subtracted. Furthermore, we subtract a flat background FBG.…”
Section: A Small Angle Neutron Scatteringmentioning
confidence: 99%
“…A strong controversy on the ''crystalline'' nature of this polymer is still open. Evidences of heterogeneous morphology have been reported, [3][4][5][6][7][8][9] but a clear interpretation of the structure is lacking. 1,10,11 On the other hand, PVC undergoes a glass transition and displays dynamical properties like the ␣and ␤-relaxations characteristic for glassforming systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…267 Interpretation of WAXS patterns of PVC seems to confirm that the crystalline phase has an orthorhombic cell formed by syndiotactic chains in the planar zig-zag configuration. 274,275 The degree of crystallinity increases with temperature of polymerization increasing and any thermal treatment during processing modifies crystallinity. 219,273 It was found that sample stretching does not modify WAXS peaks.…”
Section: Wide Angle X-ray Scattering Waxs or Waxdmentioning
confidence: 99%